User friendly concept in intelligent building case studies : Central Plaza, Wisma Cyclecarri and Menara Public Bank / Faridah Abdullah - Abdullah, Faridah (1998)
Scattered numbers of intelligent buildings are constructed within City Centre of Kuala Lumpur after years of 1990 encouraged by City Hall of Kuala Lumpur in order to introduce high quality office buildings. Rapid growth of few numbers of intelligent buildings posed one common problem how to operate and manage the intelligent features. “ Intelligent building” is the term that has been coined for this high technology building environments which employ sophisticated computer system, specialised cabling, electronic sensors and digital communication equipment so that the building condition can be centrally monitored and controlled automatically. The concept of user friendly in intelligent building is to gain actual comprehension and perception about the effectiveness of the system. It was evaluated by determined the features incorporated and how they are operated, utilised and manage. The system is friendly to users was determined through factors of convenience, comfort, safety and the BAS technician able to monitor and manage the system.